2011
DOI: 10.1007/s11518-011-5171-0
|View full text |Cite
|
Sign up to set email alerts
|

Getting to the bottom of footwear customization

Abstract: Footwear have been evaluated mostly using commercially available products, while some researchers have used custom shoes. Hence, the understanding of the effects of various parameters of a shoe is quite limited. The footbed simulator invented in recent years allows a range of parameters to be studied in quiet standing. It can be used to evaluate perceived feel and center of pressure changes to changes in heel height, seat length, material, wedge angle and toe spring. This paper is meant to show the value of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The term foot-bed refers to region of the footwear that is in close proximity and in contact with the foot. The foot-bed shape along with its design features of heel seat length and heel wedge angle contribute to maintaining postural stability (Weerasinghe & Goonetilleke, 2011; Witana, Goonetilleke, Au, Xiong, & Lu, 2009). Previous research has reported that a heel wedge angle and a heel portion of the foot-bed that promotes greater contact with the foot can aid in better foot pressure distribution and greater comfort (Witana et al, 2009).…”
Section: Minimalist Footwear Designs That Impact Postural Stability Amentioning
confidence: 99%
“…The term foot-bed refers to region of the footwear that is in close proximity and in contact with the foot. The foot-bed shape along with its design features of heel seat length and heel wedge angle contribute to maintaining postural stability (Weerasinghe & Goonetilleke, 2011; Witana, Goonetilleke, Au, Xiong, & Lu, 2009). Previous research has reported that a heel wedge angle and a heel portion of the foot-bed that promotes greater contact with the foot can aid in better foot pressure distribution and greater comfort (Witana et al, 2009).…”
Section: Minimalist Footwear Designs That Impact Postural Stability Amentioning
confidence: 99%
“…Academia considers systems of shoe personalisation (i.e. Piller, Lindgens, and Steiner, 2012;Weerasinghe and Goonetilleke 2011) and their history (Ball and Rollinson 1935;Greene 2018). Moreover, shoes were the first wearable computer (Mann 1997) and continue to fascinate HCI as a rich location for data (Schirmer et al 2015, Feijs, Nachtigall, and.…”
Section: Introductionmentioning
confidence: 99%
“…Customized and made to measure (MTM) shoes contribute to increase the foot comfort, a crucial parameter for a high customer satisfaction. Literature is full of interesting studies regarding the development of methods and tools to support the customization and personalization of shoes or shoe components (Weerasinghe and Goonetilleke, 2011). Some of them face the 3D foot shape reconstruction with the aim to maximize the shoe fitting (Zhao et al, 2008).…”
Section: Introductionmentioning
confidence: 99%